(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper, IOT with application of IOT has been explained. IoT Stands for Internet of things. It has formulated as an essential part of our daily life. IOT is any device or thing which is connected to the internet direct or indirect way. This paper also considered the challenges, limitations and scope of IOT. There is one element the trust which is necessary between user and service provider. The behaviour of nodes in trust model has been mentioned here. This paper includes the different type of attacks. There are several existing researches related to IOT and trust management which have been made in this field also mentioned in this paper.